Genetic algorithms for deriving priorities in analytic hierarchy process - 195891 Nur Farha Zakaria; Nur Farha Zakaria, 1984-, author; Halina Mohamed Dahlan, author; Ab. Razak Che Hussain, author; Muhammad Rushdi Rusli, 1984-, author; International Confrence on Software Engineering & Computer System (2009 : Kuantan , Pahang) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL